2010
DOI: 10.1128/cvi.00444-09
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Indirect Enzyme-Linked Immunosorbent Assays and IgG Avidity Assays Using a Protein A-Peroxidase Conjugate for Serological Distinction between Brucella abortus S19-Vaccinated and -Infected Cows

Abstract: This study aimed to evaluate the use of protein A-peroxidase (horseradish peroxidase [HRPO]) in indirect enzyme-linked immunosorbent assays (iELISAs) and IgG avidity assays for serological distinction betweenBrucella abortus S19-vaccinated and -infected cows. Four groups were analyzed: GI, 41 nonvaccinated seropositive cows; GII, 79 S19-vaccinated heifers analyzed at 3 months postvaccination; GIII, 105 S19-vaccinated cows analyzed after 24 months of age; and GIV, 278 nonvaccinated seronegative cows. IgG levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…melitensis , and B. suis as well in Salmonella dublin . In that sense, various immunogenic proteins can show amino acid sequences homologous to those of other bacteria, and the presence of cross‐reacting antibodies in nonvaccinated seronegative cows established on real field conditions, has to be assumed because of frequent contact with these microorganisms .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…melitensis , and B. suis as well in Salmonella dublin . In that sense, various immunogenic proteins can show amino acid sequences homologous to those of other bacteria, and the presence of cross‐reacting antibodies in nonvaccinated seronegative cows established on real field conditions, has to be assumed because of frequent contact with these microorganisms .…”
Section: Discussionmentioning
confidence: 99%
“…These findings likely indicate cross-reactivity with conserved proteins of prokaryotic microorganisms, such as the GMP synthase (spot #31) that was previously characterized in B. abortus, B. melitensis, and B. suis [31] as well in Salmonella dublin [32]. In that sense, various immunogenic proteins can show amino acid sequences homologous to those of other bacteria, and the presence of cross-reacting antibodies in nonvaccinated seronegative cows established on real field conditions, has to be assumed because of frequent contact with these microorganisms [22]. On the other hand, the antigenic spots with Mr below 20 kDa in the area (i) were recognized exclusively by GI sera, supporting the findings of 1D immunoblot that considered the three nonimmunodominant antigenic bands (10,12, and 17 kDa) as valuable candidates for the serological distinction from B. abortus infected and vaccinated cattle.…”
Section: Discussionmentioning
confidence: 99%
“…When the iELISA was compared with the competitive ELISA, both showed very high specificities (99-100%) for bovine, ovine and caprine samples from noninfected animals [17]. According to the further study by Pajuaba et al [16], the iELISA using B. abortus smooth lipopolysaccharide antigen and protein A-HPRO conjugate for preferential detection of the IgG2 subclass was shown to be suitable for serological distinction between S-19-vaccinated and S-19-infected cows, which indicates that replacement of the protein G-HPRO conjugate employed in this study by protein A conjugate may improve the system so as to differentiate naturally infected cattle from vaccinated ones.…”
Section: Discussionmentioning
confidence: 99%
“…Protein A reacts more specifically with the IgG 2 subclass, whereas protein G reacts with both subclasses of bovine IgG (IgG 1 and IgG 2), which allows detecting antibodies at any time of infection (Díaz et al, 2015;Shome et al, 2015). In comparative immunological studies on affinity and specificity of proteins A and G, protein G showed a greater affinity for G-type bovine immunoglobulins (Nielsen et al, 2004;Pajuaba et al, 2010;Genç et al, 2012). The present study showed the greater affinity of protein G for bovine immunoglobulins compared with protein A, observed in the results of sensitivity and specificity obtained by the LFIA-PG system.…”
Section: Resultsmentioning
confidence: 99%